Dualism of Foundation Governance and Its Legal Implications: A Legal Analysis of Court Decision No. 6/Pdt.G/2025/PN Agm on Civil Wrongdoing - Puspita, Dela; Mayasari, Riri Tri; Putra, Hendi Sastra; Ardinata, Mikho (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
Disputes over foundation governance in Indonesia are frequently resolved through formal administrative approaches, often overlooking the substantive legitimacy of founders and internal procedures. This study analyzes judicial reasoning in Court Decision No. 6/Pdt.G/2025/PN Agm, specifically regarding the validity of management and its alignment with the principle of legality. Utilizing normative legal methods, including statutory, conceptual, and case approaches, this research examines court decisions, legislation, and academic literature. The findings suggest that the court prioritizes administrative aspects over statutory requirements, including founders' meetings and articles of association. This leads to non-normative reasoning, including the pragmatic assumption that "whoever produces the document first prevails." Additionally, the absence of notary involvement in examining amended deeds resulted in formal defects, as notarial deeds cannot be legally assessed without the presence of the drafter. The study concludes that foundation dispute resolution must strike a balance between formal and substantive legality, while ensuring a comprehensive examination of notarial deeds. This research contributes to the discourse by highlighting the need for harmonized judicial practice and evaluating the procedural role of notaries in cases involving dual governance.